The relationship between low back pain incidence and ultrasound assessment of trunk muscles in adult soccer players: A cohort study - Noormohammadpour, P.; Aghaei-Afshar, M.; Mansournia, M. A.; Mirzashahi, B.; Akbari-Fakhrabadi, M. (Asian Journal of Sports Medicine, 2020)
Background: Few studies have demonstrated the connection between trunk muscle thickness and low back pain (LBP) in athletes.